MILD COGNITIVE IMPAIRMENT IN HEALTHY MIDDLE AGE POPULATION USING CERAD TEST - Nur Faisah Arafah; Abdul Muis; Muhammad Akbar; Amiruddin Aliah; Cahyono Kaelan; Ilhamjaya Patellongi (Journal Medical Universitas muhammadiyah Makassar, 2022)
This study aims to find out the relationship between level of education, occupation, dan number of hobbies with mild cognitive impairment in middle age. The study was conducted among healthy sample in Dr. Wahidin Sudirohusodo Hospital and its network from March to May 2012. This research is an observational study. The samples were examined using CERAD test to assess mild cognitive impairment as a dependent variable in middle age group, and were related to education level, occupation and number of hobby as an independent variables. The data were analyzed using chi square and other test according to study goals and measurement scale. The results of the study reveals significant relationship between level of education, occupation and number of hobbies (significancy for each variable : 0,000) Low education, unemployment and less number of hobbies were powerfull risks of developing mild cognitive impairment.